PENGARUH STRUKTUR MODAL DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Endah Septiani; Krisnawuri Handayani (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This study aims to analyze the effect of capital structure and liquidity on profitability in transportation and logistics sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This research uses a quantitative approach and the type of data used is secondary data. The population this study are 33 transportation and logistics sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. For the sampling technique in this study using purposive sampling method and obtained as many as 22 samples. The data source was obtained from the website www.idx.co.id. which will then be tested using multiple linear regression analysis and the SPSS 16.0 application as a tool for processing data. The independent variable in this study is the capital structure which consists of the Debt to Equity Ratio (DER) and the Debt to Asset Ratio (DAR) and liquidity consists of the Current Ratio (CR) while the dependent variable is the projected profitability by Return on Total Assets (ROA). The results of this study indicate that the variables of capital structure and liquidity together have a significant effect on the profitability variable. While the effect of capital structure (DER) on profitability (ROA) is negative and not significant. The effect of capital structure (DAR) on profitability (ROA) is negative and significant. The effect of liquidity (Current Ratio) on profitability (ROA) is positive and not significant